Korelasi Antara Konsep Diri dengan Kemampuan Pemecahan Masalah IPS - Wardani, N.M.A; Suniasih, N.W; Sujana, I.W (Universitas Pendidikan Ganesha, 2018)
This study aims to determine the correlation between self-concept with the ability to solve the problem of Social Science students of grade V elementary school Gugus Untung Surapati, East Denpasar District, academic year 2017/2018. This type of research is ex post facto, correlational research. The population of this study is a class V student in Gugus Untung Surapati, East Denpasar academic year 2017/2018 which amounted to 525 students. Determination of the sample using proportional random sampling technique with 5% error rate that obtained many samples from the population is 213 students. The data obtained through self-concept questionnaire and essay test of Social Science problem solving ability done by the respondents. Data analysis technique using product moment correlation analysis. As a prerequisite test is the normality test of data distribution. Based on the analysis result obtained rcount = 0,446. At the significance level of 5% with n = 213, then obtained rtable = 0,138. Because rcount = 0.446 > rtable = 0.138 it can be interpreted that H0 rejected and Ha accepted. So it can be concluded that there is a significant correlation between self-concept with the ability to solve the problem of Social Science Class V SD Gugus Untung Surapati, with a positive correlation direction, meaning that the higher self-concept owned by students will further improve students problem solving skills of Social Science